Asymmetric impact of exchange rate changes on money demand in Malaysia - Hussin Abdullah; Shehu El-Rasheed; Hafizah Hammad Ahmad Khan (Contemporary Economics, 2022)
The relationship between exchange rate and money demand has long been debated among macroeconomists due to its impact on the stability of money demand and monetary policy. Following the significant depreciation in the currency exchange associated with the political instability in Malaysia in recent years, examining the relationship between exchange rate and money demand is crucial to ensure the monetary policy remains prudent. This study examined the asymmetric impact of exchange rate changes on money demand in Malaysia using both linear and nonlinear ARDL approaches. The findings reveal that the money demand responds asymmetrically to exchange rate changes both in the short and long run, whereby the response to a negative shock (local currency depreciation) outweighs the positive shock (local currency appreciation). The result also suggests that the substitution effects dominate the exchange rate and money demand relationship. Consequently, with the economic and political instability continuing, the currency exchange is expected to depreciate further, contributed by the strong substitution effects. This will greatly affect the stability of money demand and the monetary policy and thereby call upon a policy intervention to strengthen the currency exchange and sustain the long-run economic performance.
Keywords: E41; E52; F31; 330; asymmetric; exchange rate; Malaysia; money demand; nonlinear ARDL